A Novel Systemic Inflammation Prognostic Score to Stratify Survival in Elderly Patients With Cancer - Ruan, Guo-Tian; Xie, Hai-Lun; Deng, Li; Ge, Yi-Zhong; Zhang, Qi; Wang, Zi-Wen; Zhang, Xi; Zhang, He-Yang; Tang, Meng; Song, Meng-Meng; Zhang, Xiao-Wei; Yang, Ming; et al. (Frontiers in Nutrition, 2022)
Background: Elderly patients with cancer face the challenge of systemic inflammation, which can lead to a poor prognosis. Existing inflammatory indices cannot fully reflect the immune-inflammatory status of patients. This study aimed to develop a new scoring system to predict the survival of elderly patients with cancer using inflammatory indices, namely the systemic inflammation prognostic score (SIPS). Methods: This prospective multicenter study included a total of 1767 patients with cancer, with a mean age of 70.97 ± 5.49 years, of whom 1170 (66.2%) were male. We performed least absolute shrinkage and selection operator (LASSO) regression to screen inflammatory indicators to include in constructing SIPS. Prognostic analysis of SIPS was performed using univariate and multivariate survival analyses. The prognostic value of SIPS and its components was compared using the prognostic receiver operating characteristic curve and concordance index. The population was divided into a training cohort and a validation cohort in a 7:3 ratio, and a SIPS prognostic analysis was performed. Results: The LASSO regression selected C-reactive protein (CRP) (≤9.81, “0”; >9.81, “1”), geriatric nutrition risk index (GNRI) (≤93.85, “1”; 93.85, “0”), advanced lung cancer inflammation index (ALI) (≤23.49, “1”; >23.49, “0”), and lymphocyte to C-reactive protein ratio (LCR) (≤2523.81, “1”; >2523.81, “0”) to develop SIPS. Patients were divided into three groups based on the total SIPS: low-risk (0), moderate-risk (1–2), and high-risk (3–4). On multivariate survival analysis, patients in the moderate-risk [P<0.001, hazard ratio (HR)=1.79, 95% confidence interval (CI): 1.47–2.17] and high-risk groups (P<0.001, HR=2.40, 95% CI: 1.98–2.92) showed a worse prognosis than those in the low-risk group. The total cohort, training cohort, and validation cohort all showed that SIPS had better survival prediction than CRP, GNRI, ALI, and LCR. The HRs were 2.81 times higher in patients in the high-risk group with malnutrition than in patients in the low-risk group without malnutrition. Conclusions: SIPS was an independent prognostic indicator in elderly patients with cancer. Malnutrition in the high-risk group increased the mortality risk.